Prenatal Cadmium Exposure Is Negatively Associated With Adiposity in Girls Not Boys During Adolescence - Moynihan, Meghan; Telléz-Rojo, Martha Maria; Colacino, Justin; Jones, Andrew; Song, Peter X. K.; Cantoral, Alejandra; Mercado-García, Adriana; Peterson, Karen E. (Frontiers in Public Health, 2019)
Introduction: Cadmium is a pervasive toxic metal that remains a public health concern and exposure in early life has been associated with growth deficits in infancy and childhood. Growth during adolescence also may be sensitive to effects of cadmium exposure, given the changes in distribution of lean and adipose tissue that vary by sex during puberty. This study examines whether prenatal and concurrent cadmium exposures are associated with adiposity measures at ages 8–15 years in a well-characterized birth cohort. Methods: The sample included 185 participants from the ELEMENT birth cohorts in Mexico City with complete data on urinary cadmium exposures, anthropometry and covariates [child age and sex, household socioeconomic status, and maternal smoking history and body mass index (BMI)]. Maternal third trimester and adolescent urines were analyzed for cadmium using an Inductively Coupled Plasma Mass Spectrometer. Trained personnel obtained anthropometry including height, weight, waist circumference and subscapular, suprailiac, and triceps skinfold thickness. BMI z-scores for age and sex were calculated using the World Health Organization's reference standard. Linear regression models were used to estimate the association of prenatal and concurrent urinary cadmium levels with adolescent anthropometry, adjusting for covariates. Results: Among 87 males and 98 females, median age was 10 years (IQR 9 –11 years). Pregnant women and children had median urinary cadmium concentrations of 0.19 μg/L (IQR 0.12– 0.27 μg/L) and 0.14 μg/L (IQR 0.11– 0.18 μg/L), respectively. Regression models showed inverse relationships between prenatal cadmium exposure and adolescent adiposity. An IQR increase in prenatal cadmium was associated with percent decreases in BMI z-score (−27%, p = 0.01), waist circumference (−3%, p = 0.01), and subscapular (−11%, p = 0.01), suprailiac (−11%, p = 0.02), and triceps (−8%, p < 0.01) skinfold thickness. When stratified by sex, these relationships remained statistically significant in females but not males. Conclusions: Prenatal cadmium exposure was negatively associated with measures of both abdominal and peripheral adiposity in girls, but not in boys. These results emphasize the sex-dependent effects of in utero cadmium exposure on adiposity in adolescence.